TEMPLE, STATE, AND SEA: GUOQING SI AND THE BUDDHIST TRANSFORMATION OF WUYUE KINGDOM (907–978 CE) - Juyi YOU; Chompoo Gotiram (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This investigation examines the intricate and multifaceted significance of Guoqing Temple in the development of the religious, political, and cultural framework of the Wuyue Kingdom (907–978 CE), recognized as one of China's most culturally vibrant regimes during the Five Dynasties and Ten Kingdoms period. Utilizing an array of textual sources, archaeological findings, empirical fieldwork data, and comparative analyses with East Asian Buddhist centers, this paper posits that Guoqing si served as both a spiritual nucleus for the Tiantai School and a pivotal node for Wuyue's political legitimization, diplomatic endeavors, and transregional artistic exchanges. This study presents a tripartite analytical framework—comprising Temple-state integration, ritual-artistic transmission, and heritage formation—to elucidate the significance of Guoqing si as a maritime center of Buddhism. The results not only shed light on the temple's distinctive contributions to statecraft and cultural diplomacy but also enrich broader discussions regarding the institutionalization of religion, the concept of sacred kingship, and the material culture of Buddhism in medieval East Asia.